Consolidation in the public sector: methods and approaches in Organisation for Economic Co-operation and Development countries. (December 2016) - Bergmann, Andreas; Grossi, Giuseppe; Rauskala, Iris; Fuchs, Sandro
Organisational changes of the public sector have led to increased decentralisation of public services. Only fully fledged financial accounting and reporting systems guarantee the consolidated information needed by executive and legislative bodies to fulfil their duties in financial management and the supervision of network entities. Consolidated financial statements may serve to increase accountability and transparency towards internal and external stakeholders. The article aims at giving an overview of consolidation approaches in Organisation for Economic Co-operation and Development countries. It will focus on the methods applied and the guiding principles followed to define the perimeter of consolidation. The analysis is carried out through a comparison of legal requirements and standards for consolidation, and the published consolidated financial statements, taking the International Public Sector Accounting Standards as a benchmark. Points for practitioners: The analysis of consolidation practice in Organisation for Economic Co-operation and Development countries reveals that while the use of consolidated financial statements is increasing, there are still significant deviations from the perspective of international accounting standards. The results show that the equity method plays a crucial role as it is used in a transition period to full consolidation and/or for organisations having major influence on the statements of financial position. These findings are of interest in the ongoing debate of international standard-setting in the field of consolidation, as well as for the discussion of European Public Sector Accounting Standards.